Effects of sevoflurane inhalation anesthesia on IL-6, TNF-Î± and MMP-9 expression and hemodynamics in elderly patients undergoing lobectomy for lung cancer - Chen, Xinyu; Li, Minjie; Zheng, Rujie; Huang, Qinfeng; Li, Yanzhen; Zhu, Yu; Chen, Zhiwei; Lin, Jianqing (Cellular and Molecular Biology, 2020)
Objective of current research was to investigate the effect of sevoflurane inhalation anesthesia on hemodynamics and inflammatory response in elderly patients with lung cancer lobectomy. Methods: A total of 168 patients with lung cancer who underwent lobectomy in our hospital from January 2019 to December 2019 were selected as the study subjects. The patients were divided into an observation group and control group according to the anesthesia program. In the control group, 1 mg/kg propofol intravenous pump induced anesthesia was maintained at 6mg/kg/h. In the observation group, 8% sevoflurane was used to induce anesthesia and 2% sevoflurane was used to maintain anesthesia. Mean artery pressure (MAP), heart rate (HR) and blood oxygen saturation (SpO2) were monitored at the beginning of single-lung ventilation (t1), when single-lung ventilation was changed to double-lung ventilation (t2), and at 30 minutes after double-lung ventilation (t3), respectively. Serum levels of interleukin-6 (IL-6), tumor necrosis factor (TNF-Î±), and matrix metalloproteinases (MMP-9) were measured using an enzyme-linked immunosorbent assay (ELISA) kit. Assess the patient’s adverse reactions. Results: At time t1 and time t2, there was no significant difference in the three hemodynamic indicators between the two groups (P>0.05). However, at t3, both MAP and HR in the observation group were significantly lower than those in the control group, while SpO2 was significantly higher than those in the control group (P<0.05). At t1 and t2, there was no significant difference in IL-6 and TNF- levels between the two groups, but at t3, IL-6 and TNF-Î± levels in the observation group were significantly lower than those in the control group (P<0.05). Compared with the control group, serum MMP-9 level was significantly decreased in the whole t1 to t3 stage (P<0.05). The incidence of complications in the observation group was significantly higher than that in the control group. It was calculated that Sevoflurane can significantly improve hemodynamics and inflammatory response in elderly patients with lung cancer lobectomy, but the incidence of complications is high.